Broadband 3-D omnidirectional magnetic induction-based sensor module for partial discharge detection of high-voltage equipment in IIoT application - Hong, Kai-Dong (2024)
Partial discharge (PD) detection is critical for diagnosing and maintaining insulation systems of high-voltage equipment. In this paper, a novel broadband three-directional (3-D) omnidirectional magnetic induction-based sensor module is proposed for non-contacting PD detection of high-voltage equipment in the Industrial Internet of Things (IIoT) application. The equivalent circuit models of a bandpass filter and planar spiral coil are comparatively investigated. Both broadband and filtering performance are realized by combining multiple spiral coils associated with the lumped capacitors. Moreover, five coils are wrapped around the dielectric cube to construct a 3-D omnidirectional sensor. Benefiting from the sub-coil interactions, the magnetic field vector is redistributed to produce a transverse component that can detect the fields parallel to the coil' s plane, thus contributing to omnidirectional sensing performance. To verify the proposed measurement technique, an IIoT-based realtime monitoring system prototype is manufactured, and the designed sensor is fabricated by using 3-D printing technology. The experiments show that the designed sensor module can achieve an ultra-wide impedance bandwidth ranging from 4 to 70 MHz (|S11|< -10 dB) while the out-of-band interference can be suppressed. Besides, the proposed system has been demonstrated for 3-D omnidirectional real-time monitoring and intelligent analysis for PD events, showcasing its significant potential in IIOT applications.